6- VS 9-MONTH RETURN TO SPORT TESTING RESULTS AFTER ACL RECONSTRUCTION WITH QUADRICEPS AUTOGRAFT IN ADOLESCENT PATIENTS. Issue 4 (28th April 2020) - Saper, Michael
Background: Recently, anterior cruciate ligament reconstruction (ACLR) using quadriceps tendon autograft has gained in popularity, particularly in adolescent patients. Studies are lacking that evaluate return to sport (RTS) testing after ACLR with quadriceps tendon autograft (QT). Hypothesis/Purpose: To investigate differences between the 6-month and 9-month RTS assessment in adolescent patients undergoing ACLR with QT. Methods: A retrospective review of adolescent patients who underwent primary ACLR with all soft-tissue QT identified 18 patients with formal RTS testing data at 6 and 9 months. Surgeries were performed between June 2017 and October 2018 by single surgeon using an all-inside technique. Concomitant meniscus repairs were performed in 38.9% of patients. All patients followed the same standardized rehabilitation protocol and completed a structured RTS test 6 and 9 months after surgery. The RTS test consisted of isometric and isokinetic strength testing, the Lower Quarter Y-Balance Test (YBT-LQ), and single-legged hop testing. The recovery of muscle strength, assessed via isometric/isokinetic and hop testing, was defined by a limb symmetry index (LSI) ≥ 90%. Differences were compared between the two RTS time points. Results: The mean age at the time of surgery was 15.2 years (range, 13-17 years). There were statistically significant improvements in the Pedi-IKDC (92.1 ± 8.4 vs. 82.9 ± 8.7; P = 0.001) and Tegner activity scale (7.1 ± 2 vs. 5.1 ± 2; P = 0.001). There were statistically significant improvements in isometric quadriceps strength (LSI, 82.6 ± 16.8 vs. 93.1 ± 11; P = 0.03) and hamstring strength (LSI, 86.4 ± 11.3 vs. 98.2 ± 9.6; P = 0.001). There were improvements in isokinetic knee extension at both 60 deg/sec (LSI, 75 ± 16.9 vs. 82.8 ± 13.9) and 180 deg/sec (LSI, 79.1 ± 14.8 vs. 84.6 ± 10.9), but the differences were not statistically significant ( P = 0.08 and P = 0.11, respectively). There were no significant differences in isokinetic testing of knee flexion at either 60 deg/sec or 180 deg/sec. There were no statistically significant differences in the anterior reach component of the YBT-LQ at 6 and 9 months. Patients demonstrated statistically significant improvements on single-legged hop testing with mean LSIs > 95% for each of the four tests at 9 months postop. Conclusion: Adolescent patients undergoing ACLR with QT demonstrated significant improvements in subjective function and quadriceps strength between 6 and 9 months postop. This data supports delaying RTS beyond 9 months in this at-risk population. : Table 1. Patient Reported Outcomes and RTS Test Results 6 Months 9 Months P* Pedi-IKDC 82.9 ± 8.7 92.1 ± 8.4 0.001* Lysholm 93.4 ± 6.8 97.2 ± 3.7 0.075 Tegner 5.1 ± 2 7.1 ± 2 0.001* Isometric-Q (LSI) 82.6 ± 16.8 93.1 ± 11 0.03* Isometric-HS (LSI) 86.4 ± 11.3 98.2 ± 9.6 0.001* Isometric-Hip (LSI) 104.9 ± 11.1 105.4 ± 7.9 0.74 Isokinetic-Q60 (LSI) 75 ± 16.9 82.8 ± 13.9 0.08 Isokinetic-HS60 (LSI) 105.5 ± 20.9 104.4 ± 24.8 0.33 Isokinetic-Q180 (LSI) 79.1 ± 14.8 84.6 ± 10.9 0.11 Isokinetic-HS180 (LSI) 97.9 ± 20.5 94.7 ± 15.2 0.7 YBT-LQ Anterior Reach (cm) 3.8 ± 5 2.3 ± 3.2 0.06 Single Hop (LSI) 90.1 ± 11.6 95.1 ± 5.7 0.01* Triple Hop (LSI) 90.3 ± 8.2 96.6 ± 4.1 0.01* Crossover Hop (LSI) 92.9 ± 13.2 97.3 ± 3.2 0.01* Timed Hop (LSI) 95.7 ± 10.9 98.4 ± 5.6 0.01* *statistically significant ( P < 0.05) Data reported as mean ± SD RTS, Return to Sport; Q, Quadriceps; HS, Hamstring; LSI, Limb Symmetry Index; YBT-LQ, Lower Quarter Y-Balance Test